Evaluation of biological activities of Physalis peruviana ethanol extracts and expression of Bcl-2 genes in HeLa cells - Çakır, Özgür; Pekmez, Murat; Cepni, Elif; Candar, Bilgin; Fidan, Kerem (Soc Brasileira Ciencia Tecnologia Alimentos, Av Brasil 2880, Caxia Postal 271 Cep 13001-970, Campinas, Sao Paulo 00000, Brazil, 2014)
Physalis species are used in folk medicine for phytotherapeutic properties. The extracts of medicinal plants are known to possess cytotoxic and chemopreventative compounds. In this study we investigated antibacterial, antioxidant, DNA damage preventative properties of Physalis peruviana (golden berry) on leaf and shoot ethanol extracts and their effects on cytotoxicity of HeLa cells and expression of apoptotic pathway genes. Among the tested bacteria for antibacterial activity, maximum inhibition zone was determined in Lactococcus lactis. The phenolic content was found higher in leaf extracts than shoot extracts. The antioxidant activity showed the highest TEAC values of the leaf (2 mg/mL) and the shoot (0.5 mg/mL) extracts as 0.291 +/- 0.04 and 0.192 +/- 0.015, respectively. In DNA damage prevention assay both leaf and shoot extracts, especially 30 and 20 mu g/mL concentrations, exhibited significant protection against DNA damage-induced by hydroxyl radical generated by Fenton reaction. Our results suggest that leaf and shoot extracts possess cytotoxic effect on HeLa cells when applied as 100 mu g/mL concentration. Also mRNA expression analysis showed the alteration of antiapoptotic genes, so the results suggest that P. peruviana ethanol extracts induce apoptotic cell death and should be investigated for identification of active compounds and their mechanisms of action.
Keywords: Bcl-2; antibacterial; antioxidant; DNA damage; HeLa; Physalis; Antibacterial Activity; Antioxidant Capacity; Induced Apoptosis; U937 Cells; Cancer; Plants; Proliferation; Angulata; Proteins; Growth